A novel ganglioside-related risk signature can reveal the distinct immune landscape of neuroblastoma and predict the immunotherapeutic response - Yang, Jiaxing; Han, Lei; Sha, Yongliang; Jin, Yan; Li, Zhongyuan; Gong, Baocheng; Li, Jie; Liu, Yun; Wang, Yangyang; Zhao, Qiang (Frontiers in Immunology, 2022)
Background: Gangliosides play an essential role in cancer development and progression. However, the involvement of gangliosides in the prognosis and tumor microenvironment (TME) of neuroblastoma is not entirely understood. Methods: Consensus clustering analysis was performed to identify ganglioside-mediated molecular subtypes. LASSO-Cox analysis was conducted to identify independent prognostic genes, and a novel risk signature was constructed. The risk signature was validated internally and externally. We further explored the independent prognosis value, immune landscape, drug susceptibility, and tumor dedifferentiation of the risk signature. The role of signature gene B3GALT4 in neuroblastoma was explored in vitro. Results: Seventeen ganglioside-related genes were differentially expressed between INSS stage 4 and other stages, and two ganglioside-related clusters with distinct prognoses were identified. A novel risk signature integrating ten ganglioside-related prognostic genes was established. Across the train set and external validation sets, the risk signature presented high predictive accuracy and discrimination. The risk signature was an independent prognostic factor and constructed a nomogram combining multiple clinical characteristics. In the high-score group, the deficiency in antigen processing and presenting machinery, lack of immune cell infiltration, and escaping NK cells contributed substantially to immune escape. The low-score group was more responsive to immune checkpoint blockade therapy, while the high-score group showed substantial sensitivity to multiple chemotherapeutic drugs. Besides, the risk score was significantly positively correlated with the stemness index and reduced considerably in all-trans retinoic acid-treated neuroblastoma cell lines, indicating high dedifferentiation in the high-score group. Additionally, neuroblastoma cells with downregulation of B3GALT4 present with increased proliferation, invasion and metastasis abilities in vitro. Conclusion: The novel ganglioside-related risk signature highlights the role of ganglioside in neuroblastoma prognosis and immune landscape and helps optimize chemotherapy and immunotherapy for neuroblastoma.